POTENSI ISOLAT MIKROBIA ASAL ANDISOL DIENG, JAWA TENGAH SEBAGAI INOKULUM PUPUK HAYATI PENGOKSIDASI SULFUR - Sudadi Sudadi; Ika Ernawati; Sumarno Sumarno; Widyatmani Sih Dewi; Hery Widijanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2013)
Title : Study on The Potency of Soil Microbes Isolated from Andisols of Dieng, Central Java,  as S-Oxidizing Biofertilizer Inoculant. The problem of nutrient deficiences tend to increase, including sulfur deficiency. The use of high purity NPK fertilizers stimulate sulfur deficiency in agricultural land. This problem can be corrected by the use of elemental sulfur accompanied with S-oxidizing biofertilizer. The study aimed to evaluate the potential of sulfur oxidizing microbial isolated from Andisols of Dieng Central Java as S-oxidizing inoculant. Andisols Dieng naturally contains high sulfur that allegedly inhabited many sulfur-oxidizing microbials. The research consisted of two experiments, each arranged in completely randomized design (CRD). Each experiment consist of two factors namely the kind of microbial isolated from Andisols Dieng and incubation time. The first experiment used Czapek-dox+elemental sulfur medium, while the second experiment used vermicompost as medium. The observed variables include soluble-S, bacterial density, biomass of fungi and medium pH. One isolate of bacteria (I1)and three isolates of fungi (F1, F2 and F3) taken from Andisol of Dieng showing their ability to oxidize sulfur in Czapek-dok agar medium. They were used as isolates in the experiment. The result of the first experiment showed that the oxidized sulfur increased with the length of incubation time as indicated by the increase of soluble-S, bacterial cell density or fungi biomass in the medium followed by the decrease of pH. The second experiment showed that the population of bacteria or fungi isolates and soluble-S of vermicompost were increased collaterally with incubation time. The fungi isolate of F2 have the highest potency as inoculant of S-oxidizing biofertilizer as shown by it ability to survive, grows and oxidize S both in Czapek-dox+elemental sulfur liquid medium as well as in vermicompost medium.